2019
DOI: 10.1016/j.dadm.2019.05.002
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal thickness as a potential biomarker in patients with amyloid‐proven early‐ and late‐onset Alzheimer's disease

Abstract: Introduction Retinal thickness measured with optical coherence tomography has been proposed as a noninvasive biomarker for Alzheimer's disease (AD). We therefore measured retinal thickness in well-characterized AD and control participants, considering ophthalmological confounders. Methods We included 57 amyloid-proven AD cases and 85 cognitively normal, amyloid-negative controls. All subjects underwent retinal thickness measurements with spectral domain optical coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
2
18
1
Order By: Relevance
“…However, den Haan et al (2018) found no retinal thinning in amyloid + AD patients. Further studies found that retinal thickness cannot discriminate between healthy individuals and preclinical AD individuals ( den Haan et al, 2019a , b ). In a recent study involving 930 participants (414 cognitively healthy people, 192 with probable amnestic MCI, and 324 probable AD patients), the results showed that there were no significant differences in retinal thickness in different layers ( Sánchez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, den Haan et al (2018) found no retinal thinning in amyloid + AD patients. Further studies found that retinal thickness cannot discriminate between healthy individuals and preclinical AD individuals ( den Haan et al, 2019a , b ). In a recent study involving 930 participants (414 cognitively healthy people, 192 with probable amnestic MCI, and 324 probable AD patients), the results showed that there were no significant differences in retinal thickness in different layers ( Sánchez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…This study suggested that RNFL, IPL and GCL changes might be useful for AD diagnosis, however Bruch's membrane opening-minimum rim width (BMO-MRW) remained unchanged. Thus, advancements in ocular imaging have provided evidence of inner retinal thinning and loss of the retinal nerve fiber layer (RNFL) in AD and its preclinical and prodromal stages, although some studies have also suggested a non-significant relationship between the effects of AD and changes in retinal imaging by OCT (den Haan et al, 2019;Haan et al, 2019a;Sanchez et al, 2020;Sanchez et al, 2018). An initial meta-analysis concluded that there was a significant RNFL thinning in early stages of AD (Knoll et al, 2016).…”
Section: Retinal Structural Changes In Ad Patientsmentioning
confidence: 99%
“…Their findings suggested that cerebral cortical changes were reflected in the retina. However, absence of retinal thinning in amyloid proven AD patients was reported in their studies [27,28]. Further studies are needed to evaluate the correlation between RNFL and AD.…”
Section: Discussionmentioning
confidence: 89%